712 SBT6290, a systemically administered Nectin-4-directed TLR8 ImmunoTAC (TM) therapeutic, is a potent human myeloid cell agonist for the treatment of Nectin-4-expressing tumors. (9th November 2020) - Metz, Heather; Brender, Ty; Stevens, Brenda; Winship, Damion; Brevik, Jamie; Comeau, Michael; Childs, Monica; Chang, Jenny; Fan, Li-Qun; Xu, Hengyu; Grey, Jonathan; Adamo, Jeffrey; et al.
Abstract : Background: SBT6290 is a novel therapeutic comprised of a selective TLR8 agonist conjugated to a Nectin-4-specific monoclonal antibody, designed for systemic delivery and tumor-localized activation of myeloid cells. Nectin-4 is a cell surface adhesion molecule that is overexpressed in multiple solid tumor types including triple negative breast, head and neck, lung, and urothelial cancers, with limited expression in normal tissues. Many solid tumors, including those expressing Nectin-4, are resistant to immunotherapy due to immune-suppressive mechanisms, loss of HLA, low neoantigen availability, and/or minimal T cell infiltrates. These tumors, however, are often replete with myeloid cells. Activation of these cells has emerged as a promising approach in overcoming resistance mechanisms to current cancer immunotherapies. TLR8 is highly expressed in myeloid cell types prevalent in human tumors, including conventional DCs and macrophages. Agonism of TLR8 in human myeloid cells activates a broad spectrum of anti-tumor immune mechanisms, including proinflammatory cytokine production, repolarization of suppressive myeloid cells, and the priming of CTL responses. Here, we show that SBT6290 potently activates human myeloid cells in a Nectin-4-dependent manner and that a mouse surrogate confers single agent anti-tumor activity in preclinical studies. These data support the development of SBT6290 for the treatment of patients with Nectin-4-expressing tumors. Methods: SBT6290 activity was characterized in vitro using co-culture systems consisting of human immune cells and Nectin-4-expressing tumor cells. The in vivo efficacy of the SBT6290 surrogate was evaluated as a single agent in mouse tumor models expressing Nectin-4. Results: Studies with human immune cells show that SBT6290 potently induces multiple anti-tumor immune activities including proinflammatory cytokine and chemokine production, inflammasome activation, direct activation of DCs and indirect T and NK cell cytolytic activity. This activity requires the presence of Nectin-4 expressing tumor cells and the engagement of Fc gamma receptors on the surface of the myeloid cells by the conjugate to facilitate delivery of SBT6290 into myeloid cells. Notably, SBT6290 is >100 fold more potent than the free, unconjugated TLR8 agonist. Systemic administration of a SBT6290 surrogate in mice results in robust single agent efficacy in tumor models intrinsically resistant to checkpoint blockade, including the EMT6 model engineered to express human Nectin-4. Conclusions: The preclinical data described here show the potential for SBT6290 to drive robust, single agent anti-tumor responses and support the clinical development of SBT6290 for patients with Nectin-4 expressing tumors.